Оптимизация систем терморегулирования космических аппаратов с использованием нечетких множеств - Гакал, П. Г. (НТУ "ХПИ", 2010)
It was proposed to carry out a thermal control system of spacecrafts optimization using fuzzy sets theory, that allowing to provide a global efficiency factor forming on the base of particular efficiency factors in the case of them fuzzy setting.
Keywords: оборудование КА; отвод теплоты; показатели эффективности; спутник телекоммуникационный